Long-segment common carotid occlusion presenting with limb-shaking transient ischemic attack: Case report - Jiang, Qingjun; Bai, Jun; Nie, Shaojie; Jin, Jie; Qu, Lefeng (Frontiers in Surgery, 2023)
Background Limb-shaking transient ischemic attack (LS-TIA) is a rare manifestation of carotid artery occlusion. Common carotid artery occlusion (CCAO) is a relatively rare condition, and both its natural history and recommendations for treatment are still unclear. Case description A 67-year-old female suffered from transient episodes of unilateral limb shaking. Computer tomographic angiography (CTA) showed long-segment occlusion of the right common carotid artery. Computer tomographic perfusion (CTP) demonstrated hypoperfusion of the corpus striatum, which suggests that hemodynamic failure is a potential mechanism underlying the LS-TIA secondary to common carotid artery occlusion. The occlusion was successfully recanalized by retrograde common carotid endarterectomy, and the episodes of left limb shaking disappeared after surgery. Conclusions The occlusion was successfully recanalized by retrograde common carotid endarterectomy, and the episodes of left limb shaking disappeared after surgery. Hypoperfusion of the corpus striatum might be a potential mechanism underlying the LS-TIA secondary to common carotid occlusion.